Personality, motives and learning environment as foundation of self-determined learning motivation - Müller, Florian H. (Array, 2006)
This study interrogates the question how personality, motives for studying and the perceived learning environment explain self-determined learning motivation in higher education. Previous research has predominantly focused on the interrelation between learning environment and self-determined motivation or on the outcomes of self-determined learning motivation. Whereas the question whether relatively stable personality dispositions preform self-determined learning motivation has been largely neglected. As a theoretical foundation of this study serve the differential psychology model, "the Big Five” model (Goldberg, 1999), as well as Deci and Ryan’ s (2002a) self-determination theory. In regression analyses, we examined the data of 724 students: their personality traits (Big Five), their study motives and their evaluation of the teaching-learning environment, focusing on how these aspects can predict forms of more or less self-determined learning motivation (cf. Deci & Ryan, 2002a). The results of the hierarchical regression analysis show that the personality dimensions conscientiousness, neuroticism and openness explain a large part of the variance of learning motivation and that the additional clarification of motives to study and the learning environments is significant.